Differences in motor activation of voluntary and reflex cough in humans. Issue 8 (6th April 2006) - Lasserson, D; Mills, K; Arunachalam, R; Polkey, M; Moxham, J; Kalra, L
Abstract : Objectives: To study motor activation patterns of voluntary and reflex cough adjusted for cough flow rates. Methods: Surface electromyography (EMG) and cough flow rate were measured in 10 healthy volunteers. Voluntary cough was assessed for 20 efforts in each quintile of increasing cough flow rate. Reflex cough was assessed for 25 efforts produced by nebulised l -tartaric acid. EMG was recorded over the expiratory (rectus abdominis, obliques, lower intercostals) and accessory (trapezius, pectoralis major, deltoid, latissimus dorsi) muscles. EMG activity, burst duration and onset were compared for each quintile of voluntary cough, and between voluntary and reflex cough matched for cough flow rate. Results: EMG activity and burst duration of expiratory and accessory muscles during voluntary cough increased in proportion to cough flow. Expiratory muscles had longer EMG burst duration (difference 68 ms (95% CI 34 to 102), p<0.01) and earlier onset of EMG activity (difference 44 ms (95% CI 20 to 68), p<0.0001) compared with accessory muscles. EMG activity in all muscles was increased (mean 110.2% v 56.1%, p<0.001) and burst duration (mean 206 ms v 280 ms, p = 0.013) decreased in reflex cough compared with voluntary cough of equal flow rate. There were no differences in EMG onset (difference 8 ms (95% CI 25 to −9) or burst duration (difference 27 ms (95% CI 58 to −4) between expiratory and accessory muscles. Conclusions: Functional organisation of motor activity differs between voluntary and reflex cough. Voluntary cough is characterised by sequential activation whereas reflex cough is associated with early and simultaneous activation of expiratory and accessory muscles.